Un schéma de type volumes finis pour résoudre les équations de Navier-Stokes sur une triangulation - Boivin, Sylvain; Hérard, Jean-Marc (European Journal of Computational Mechanics, 1996)
We present a new scheme to solve the Navier-Stokes equations for incompressible flows, together with a convection-diffusion equation of a passive scalar. The numerical solution is searched in an approximation based on the RT0 finite element. Controle volumes are defined by triangles ; both global and local conservation of mass and passive scalars, and the maximum principle, are ensured by approximate convection-diffusion operator. The numerical pressure is unique/y defined, up to a constant.